Analysis of Environmental Awareness Profiles in Fifth Grade Students at Elementary School Two Bumirejo Kebumen - Karim, Ade Nofita; Rahman, Alvin; Triyaningsih, Wiwit; Zuhriyah, Lailatul Malikatus; Pramono, Ibnu Jati; Sabitussolikhah, Nurul; Fitriyah, Nurul; Istianah, Lailatul; Fatimah, Siti; Trisnawati, Oky Ristya; Maryanto, Maryanto; Nurhidayah, Nurhidayah (Proceeding International Conference on Religion, Science and Education, 2025)
Environmental care is an effort to protect the environment and its sustainability. The purpose of this study was to analyze the environmental care profile of fifth grade students of State Elementary School 2 Bumirejo on student attitudes. This research is aquantitative research. Data collection instrument with survey method, using questionnaire or questionnaire technique. The subjects of this study were 25 fifth grade students. The data collection technique used a semi-closed questionnaire. Data analysis techniques using descriptive techniques. The results of the analysis show that students' environmental awareness is in the good category with an average score of 89.6%. The first aspect of understanding environmental concepts is 94%, the second aspect of recognizing environmental issues is 90%, the third aspect of participation in environmental conservation is 84%, and the fourth aspect of awareness of individual responsibility is 87.5%. Of these aspects, the highest aspect in this study is the understanding of environmental concepts with a percentage of 94%. While the aspect with the lowest percentage of 84% is the aspect of participation in environmental conservation efforts. Based on the results of the analysis, grade V students have good environmental awareness.